2021
DOI: 10.1016/j.heliyon.2021.e07519
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic profile in index patients with spinocerebellar ataxia type 3 in Indonesia: case report

Abstract: Spinocerebellar ataxia (SCA) is an autosomal dominant hereditary disease with progressive course, and no causal therapy. Diagnostics are still challenging, due to facility and protocols, and so as in Indonesia. As a national referral center, Dr. Hasan Sadikin Central General Hospital has received a lot of patients from all over Indonesia, particularly from Western Java. Study related to SCA (including clinical and genetic profile) is still limited in Indonesia. We identified index patients from three families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The online CA group also showed an impairment relative to controls, consistent with prior findings [51]. Notably, our CA group scored significantly higher on the MoCA relative to values reported in previous studies with this population [49][50][51]. The reason for this difference is not clear.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The online CA group also showed an impairment relative to controls, consistent with prior findings [51]. Notably, our CA group scored significantly higher on the MoCA relative to values reported in previous studies with this population [49][50][51]. The reason for this difference is not clear.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, the MoCA scores for the PD group were not significantly different from the composite, in-person mean (PD = 27.0, µ = 26.8, t = 0.63, SD = 2.4, p = 0.530, effect size = 0.04) [12,13,48]. However, the CA group scored significantly higher than the composite mean from in-person studies (CA = 26.0, µ = 23.6, t = 5.97, SD = 5.6, p < 0.001, effect size = 0.52) [49][50][51]. Comparisons between our online groups (Table S1) revealed that both patient groups performed worse than the controls on the MoCA test (PD vs. controls: t = −2.01, p = 0.047, effect size = 0.37; CA vs. controls: t = −3.73, p < 0.001, effect size = −0.73).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation